MOF-derived CoFe alloy nanoparticles encapsulated within N, O Co-doped multilayer graphitized shells as an efficient bifunctional catalyst for zinc–air batteries. Issue 28 (4th July 2022) - Zhang, Jingjing; Tang, Fumin; Wan, Kechuang; Yang, Yange; Zhang, Cunman; Ming, Ping Wen; Li, Bing
Abstract : Metal–organic frameworks (MOFs) and their derivatives are promising electrocatalysts for zinc–air batteries due to their advantages of reconfigurable metal nodes and abundant coordinatively unsaturated active sites. Abstract : Metal–organic frameworks (MOFs) and their derivatives are promising electrocatalysts for zinc–air batteries due to their advantages of reconfigurable metal nodes and abundant coordinatively unsaturated active sites. However, current MOF-derived composites are mostly microporous and have low graphitization, which are deemed unfavourable for ion and electron transport. Herein, we report CoFe alloy nanoparticles encapsulated in N, O co-doped multilayer graphitized shells as effective bifunctional catalysts as well as the simple and practical preparation of cobalt/iron MOFs and their subsequent carbonization. The resulting heteroatom-doped carbon highly graphitized bimetallic catalysts were examined by electrochemical tests and deliver a minimum Δ E (Δ E = E j10 − E 1/2 ) of 0.678 V and exhibits high durability after long-term testing. The homemade zinc–air battery has a high power density (>200 mW cm −2 ) with a high specific capacity (829.5 mA h g −1 ). In addition, the zinc–air battery exhibits high stability during battery cycling processes. Therefore, this work provides a promising pathway for advanced metal–air cathode materials.